PENGARUH MODAL KERJA DAN LAMA USAHA TERHADAP PENDAPATAN USAHA TANAMAN HIAS DI DESA PETIGA KECAMATAN MARGA KABUPATEN TABANAN - SUDARSANI, NI PUTU (Universitas Mahasaraswati Mataram, 2019)
This study aims to determine the effect of working capital and business variables on the income of ornamental plant business in Petiga Village, Marga District, Tabanan Regency. This study takes a sample of 64 respondents. The analytical tool used is multiple linear regressions. Based on the results of the calculation of SPSS 22.00, the calculated F value is 31,088 with a significance of F of 0,000. By using a 0.05 level of significance obtained F table value of 3.15, then F count (31.088)> F table (3.15), or the significance of F of 0.000 shows smaller than 0.05 so it can be concluded that the two independent variables i.e. working capital and length of business jointly influence the amount of income of ornamental plant business in Petiga Village, Marga Subdistrict, Tabanan Regency is accepted. Partially the working capital variable has a significant effect. While the duration of business influences the income of the business of ornamental plants in Petiga Village, Marga District, Tabanan Regency, but it is not significant